Decreased Gray-Matter Volume in Insular Cortex as a Correlate of Singers’ Enhanced Sensorimotor Control of Vocal Production - Wang, Wenda; Wei, Lirao; Chen, Na; Jones, Jeffery A.; Gong, Gaolang; Liu, Hanjun (Frontiers in Neuroscience, 2019)
Accumulating evidence has shown enhanced sensorimotor control of vocal production as a consequence of extensive singing experience. The neural basis of this ability, however, is poorly understood. Given that the insula mediates motor aspects of vocal production, the present study investigated structural plasticity in insula induced by singing experience and its link to auditory feedback control of vocal production. Voxel-based morphometry (VBM) was used to examine the differences in gray matter (GM) volume in the insula of 21 singers and 21 nonsingers. An auditory feedback perturbation paradigm was used to examine the differences in auditory-motor control of vocal production between singers and nonsingers. Both groups vocalized sustained vowels while hearing their voice unexpectedly pitch-shifted -50 or -200 cents (200 ms durtion). VBM analyses showed that singers exhibited significantly lower GM volumes in the bilateral insula than nonsingers. When exposed to pitch perturbations in voice auditory feedback, singers involuntarily compensated for pitch perturbations in voice auditory feedback to a significantly lesser degree than nonsingers. Moreover, across the two sizes of pitch perturbations, the magnitudes of vocal compensations were positively correlated with the total regional GM volumes in the bilateral insula. These results indicate that extensive singing training leads to decreased GM volumes in insula and suggest that morphometric plasticity in insula contributes to the enhanced sensorimotor control of vocal production observed in singers.